An Unusual Cause of Acute Isolated Hepatitis in a Cancer Patient Post-COVID Pneumonia: HSV-2 - Ozturk-Kaygusuz, Tuerkkan; Sagmak-Tartar, Ayse; Akbulut, Ayhan (Doc Design Informatics Co Ltd, 2022)
Herpes simplex virus is a rare cause of hepatitis in immunosuppressed and immunocompetent individuals. It can cause clinical pictures in patients ranging from an asymptomatic course to fatal acute fulminant hepatitis. Early diagnosis and treatment may be delayed if it is not suspected because of the patients' nonspecific clinic. This study presents a case of isolated HSV-2 hepatitis in a patient with a history of cancer chemotherapy and a recent diagnosis of COVID-19 who received steroid therapy.
Keywords: herpes simplex virus infections; herpes simplex virus-2; hepatitis; COVID-19